A core syllabus for the teaching of embryology and teratology to medical students. Issue 2 (25th November 2016) - Fakoya, Francis A.; Emmanouil‐Nikoloussi, Elpida; Sharma, Deepak; Moxham, Bernard J.
Abstract : Clinical relevance in the teaching of biomedical sciences within health care courses presupposes that there is internationally agreed core material within the curricula. However, with the exception of a syllabus for neuroanatomy and gross anatomy of the head and neck for medical students, core syllabuses within many of the specialized anatomical sciences have yet to be developed. The International Federation of Associations of Anatomists aims to formulate internationally accepted core syllabuses for all anatomical sciences disciplines initially using Delphi Panels that comprise anatomists, scientists, and clinicians who evaluate syllabus content. Here, the suggestions of a Delphi Panel for embryology and teratology are presented prior to their publication on the website of the International Federation of Associations of Anatomists. Hence, to obtain a more definitive syllabus, it is required that anatomical and embryological/teratological societies, as well as individual anatomists, embryologists and clinicians, freely comment upon, elaborate and amend, this draft syllabus. The goal is to set internationally recognized standards and thereby provide guidelines concerning embryological and teratological knowledge when involved with course development. Clin. Anat. 30:159–167, 2017. © 2016 Wiley Periodicals, Inc.